2011
DOI: 10.2106/jbjs.j.01252
|View full text |Cite
|
Sign up to set email alerts
|

Managing Stress in the Orthopaedic Family

Abstract: Stress is a double-edged sword. When managed appropriately, it can lead to peak performance in high-pressure professions, while the potential negative effects of stress are well documented, being directly related to seven of the ten leading causes of death in industrialized nations 1,2 .A major psychological manifestation of stress is burnout. Validated assessment tools, such as the Maslach Burnout Inventory, can be utilized to quantify the three components of burnout: emotional exhaustion, depersonalization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…This challenges the common belief that surgical specialties carry a higher prevalence of burnout due to increased hours and a more stringent call schedule. A 2011 study of 384 orthopaedic surgery residents and 264 full-time orthopaedic surgery faculty reported residents work an average of 74.2 +/-20.2 hours per week and faculty 62.8 +/-18.2 hours per week [9]. This is compared to a 2013 study which found that 76% of anesthesiology residents work less than 70 hours a week and 24% work more than 70 hours per week.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This challenges the common belief that surgical specialties carry a higher prevalence of burnout due to increased hours and a more stringent call schedule. A 2011 study of 384 orthopaedic surgery residents and 264 full-time orthopaedic surgery faculty reported residents work an average of 74.2 +/-20.2 hours per week and faculty 62.8 +/-18.2 hours per week [9]. This is compared to a 2013 study which found that 76% of anesthesiology residents work less than 70 hours a week and 24% work more than 70 hours per week.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of three hundred and eighty-four orthopaedic surgery residents, Sargent, et al, found that 60% reported having at least one mentor. Levels of emotional exhaustion decreased and personal achievement increased as the frequency of contact between mentor and mentee increased [9]. Higher personal achievement, lower emotional exhaustion, and lower depersonalization scores were also found in those who reported it helpful to speak with their mentors [7].…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is a maladaptive syndrome specific to the workplace that results from chronic work stress. 10 -12 According to Maslach et al, burnout has three dimensions: emotional exhaustion, a feeling of one’s energy being depleted due to excessive psychological and emotional demands; depersonalization, a tendency to be detached from others, and view others in an impersonal or cynical manner; and a diminished sense of personal accomplishment, or feelings of inadequacy in the work environment. 13 The current “gold standard” for burnout assessment is the Maslach Burnout Inventory.…”
Section: What Is Burnout?mentioning
confidence: 99%
“…So, they should not only be intelligent, but they must also have strong training, mentoring, and experience. 29,30 The burnout syndrome has been defined as a state of physical emotional or mental exhaustion caused by longterm involvement in situations that are emotionally demanding. We all know that due to increasing number of surgeries and lack of surgeons, staff shortage, high work overload, surgeons frequently experience stress, burnout, emotional exhaustion, depersonalization, and reduced personal achievements at the workplace.…”
Section: Psychological Hazardmentioning
confidence: 99%